Improving the Sensitivity of SPR Sensors with Au–Ag alloys and 2D Materials — a Simulation‐Based Approach. Issue 12 (10th November 2021) - Das, Chandreyee Manas; Guo, Yan; Kang, Lixing; Poenar, Daniel Puiu; Xiong, Jiaqing; Ramaswamy, Yogambha; Martinez‐Martin, David; Yong, Ken‐Tye
Abstract: Plasmonic‐based sensing revolves around the generation of plasmons as a result of light–matter interactions. Analytical and/or diagnostic technologies based on this principle are extremely successful and popular in the bio‐medical industry due to their high sensitivity as well as real‐time and label‐free sensing capabilities. Employing 2D multilayers as the main plasmonic substrate instead of pure metals is a relatively new concept that can provide advantages for the surface plasmon resonance (SPR) sensor. In this work, the gain in sensitivity of the Au–Ag based SPR sensors is evaluated by employing 2D materials like graphene, MoS2, and WS2 in a multilayer SPR system. The simulations calculate the sensitivity of such multi‐layered SPR structures and indicate that the use of WS2 in the modified system can lead to an increased sensitivity (1.53 times) as compared to the standard Au‐based Kretschmann configuration. Abstract : Biological surface plasmon sensing based on standard Au Kretschmann configuration has been around for many years. However, here, a systematic simulation study of Au–Ag alloy based surface plasmon resonance sensors and how 2D materials like graphene, MoS2, and WS2 can be effectively used to boost the basic sensitivity of these revolutionary sensors, is presented.